Knowledge management on response times to the information technology requirements - Cajacuri Pacheco, Sulla Rocío (2024)
To identify the most relevant factors that a knowledge management model (KM model) should consider to contribute to the satisfaction of the response times to the information technology requirements (RTITR) of a financial institution in Lima (Peru) was the main objective of the research, for this a quantitative approach was considered in which the ordinal logistic regression analysis was applied to a sample consisted of 31 specialists from the systems area of the financial institution under study to whom the questionnaire was applied to identify the necessary factors according to their relevance in the KM model to contribute to the satisfaction of the RTITR which has been the concern of the specialists from the systems area to generate fast responses, therefore, with the ordinal logistic regression analysis using the significance and orientation of coefficients, the most relevant factors that the KM model should consider to contribute to the satisfaction of the RTITR were identified, concluding that the most relevant factors to be considered by the KM model are the information and communication technology – information management (ITCIM), and the knowledge, people and culture management strategy (KPCMS).